2016
DOI: 10.1155/2016/2029854
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Impairs Insulin Secretion of Pancreaticβ-Cells through Increased Production of ROS and Mitochondrial Dysfunction Mediated by Upregulation of UCP2 and MAPKs

Abstract: Methylglyoxal (MG) is a highly reactive glucose metabolic intermediate and a major precursor of advanced glycation end products. MG level is elevated in hyperglycemic disorders such as diabetes mellitus. Substantial evidence has shown that MG is involved in the pathogenesis of diabetes and diabetic complications. We investigated the impact of MG on insulin secretion by MIN6 and INS-1 cells and the potential mechanisms of this effect. Our study demonstrates that MG impaired insulin secretion by MIN6 or ISN-1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
(48 reference statements)
2
35
0
Order By: Relevance
“…We detected apoptotic cells and apoptotic proteins, The results showed that IRI can effectively upregulate the production of the apoptotic protein caspase 3. Some studies have focused on the use of proprietary Chinese medicines for the antioxidation and anti-apoptosis relief of IRI, but the effects of these exogenous treatments are uneven and have a detrimental effect on other tissues (Bo et al, 2015;Hill et al, 2008;Lin et al, 2003). Thus, the activation of endogenous protection is still the focus of research.…”
Section: Discussionmentioning
confidence: 99%
“…We detected apoptotic cells and apoptotic proteins, The results showed that IRI can effectively upregulate the production of the apoptotic protein caspase 3. Some studies have focused on the use of proprietary Chinese medicines for the antioxidation and anti-apoptosis relief of IRI, but the effects of these exogenous treatments are uneven and have a detrimental effect on other tissues (Bo et al, 2015;Hill et al, 2008;Lin et al, 2003). Thus, the activation of endogenous protection is still the focus of research.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of MIN6 (mouse insulinoma cells) and INS1 (rat insulinoma cells) cells after 3 h of MG incubation with either 0.05 or 0.1 mM revealed decreased insulin secretion when stimulated with 5 mM or 25 mM glucose compared to control cells [61]. Furthermore, 0.1 mM, but not 0.05 mM of MG induced apoptosis in MIN6 cells.…”
Section: Effects On Murine Pancreatic β-Cellsmentioning
confidence: 97%
“…UCP2 facilitates proton leakage to reduce the MMP and thus to reduce ATP generation. Reduced ATP production ultimately results in β-cell dysfunction [61,62,64].…”
Section: Effects On Murine Pancreatic β-Cellsmentioning
confidence: 99%
“…Excessive insulin cannot be utilized by the cells, which inhibit glucose uptake in adipose tissue and increase inflammatory cytokines (Qatanani and Lazar, 2007). Previous studies have shown that the plasma concentrations of advanced glycation end products (AGEs) and methylglyoxal (MG) are increased in obesity and in patients with insulin resistance (Bo et al, 2016). Furthermore, long-term intake of AGEs and MG could increase AGEs and MG levels in the body, and circulating of AGEs in the body is not easily eliminated (Sims et al, 2010;Tikellis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%